2006
DOI: 10.1121/1.4781377
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual perception of voicing with age in quiet and cafe noise

Abstract: Research has shown that voicing is difficult to discern in noisy environments. While voicing may be difficult to resolve from visual cues, acoustic cues for voicing are relatively robust. This study addresses these factors with normally aging audiovisual perception. Identification responses were gathered with 19–30-year-old and 49–60-year-old adults for audiovisual (AV) CVs differing in voicing and consonant place of articulation. Materials were presented in quiet and in cafe noise (SNR=0 dB) as audio-only (A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Different phonetic attributes, in this respect POA and voicing, are associated with different vulnerabilities to noise. A prior study by Behne et al ͑2006͒ showed that for AV stimuli differing in POA, babble noise at a SNR of 0 dB led to an increase in the use of the visual modality, whereas no such shift was evident for AV stimuli that vary in voicing at this noise level. These results are supported by a firm body of research ͑e.g., Jiang et al, 2006;Miller and Nicely, 1955͒.…”
Section: Noise Signalmentioning
confidence: 85%
See 4 more Smart Citations
“…Different phonetic attributes, in this respect POA and voicing, are associated with different vulnerabilities to noise. A prior study by Behne et al ͑2006͒ showed that for AV stimuli differing in POA, babble noise at a SNR of 0 dB led to an increase in the use of the visual modality, whereas no such shift was evident for AV stimuli that vary in voicing at this noise level. These results are supported by a firm body of research ͑e.g., Jiang et al, 2006;Miller and Nicely, 1955͒.…”
Section: Noise Signalmentioning
confidence: 85%
“…Surprisingly, voiced consonants resulted in more A-match responses ͑M = 45%, SE = 2.8͒ than did voiceless consonants ͑M = 23%, SE = 2.65͒. This result contrasts with previous findings ͑e.g., Behne et al, 2006;McGurk and MacDonald, 1976͒. The most remarkable observation in this respect is the size of the difference in mean A-match responses between voiced and voiceless consonants, and the voicing effect's consistency across conditions.…”
Section: Poa Stimulimentioning
confidence: 94%
See 3 more Smart Citations